2001
DOI: 10.1038/sj.bjp.0704100
|View full text |Cite
|
Sign up to set email alerts
|

Regional haemodynamic responses to the cannabinoid agonist, WIN 55212‐2, in conscious, normotensive rats, and in hypertensive, transgenic rats

Abstract: 1 Regional haemodynamic responses to the cannabinoid agonist, WIN 55212-2 (5 ± 250 mg kg 71 i.v.) were assessed in conscious, normotensive, Hannover, Sprague-Dawley (HSD) rats, and in hypertensive, transgenic ((mRen-2)27) (abbreviated to TG) rats. 2 In HSD rats, WIN 55212-2 caused pressor, and renal and mesenteric vasoconstrictor eects, with a hindquarters vasodilator eect occurring only at the highest dose. In TG rats, the eects of the cannabinoid agonist were qualitatively similar to those seen in HSD rats, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 30 publications
5
41
0
1
Order By: Relevance
“…Indeed, the pro®le of cardiovascular eects of anandamide resembled, in several respects, those of 5-HT, which triggers the von Bezold-Jarisch re¯ex through stimulating 5-HT 3 -receptors on vagal aerent ®bres, with subsequent vagal eerent activation (Veelken et al, 1998). The only vascular bed to show vasodilatation in response to anandamide was the hindquarters, which is consistent with the eects of the synthetic cannabinoid, WIN 55212-2, in our model (Gardiner et al, 2001;2002a, b). We have shown that the hindquarters vasodilator responses to WIN 55212-2 are sensitive to CB 1 -receptor antagonism, and involve b 2 -adrenoceptors (Gardiner et al, 2002a, b).…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Indeed, the pro®le of cardiovascular eects of anandamide resembled, in several respects, those of 5-HT, which triggers the von Bezold-Jarisch re¯ex through stimulating 5-HT 3 -receptors on vagal aerent ®bres, with subsequent vagal eerent activation (Veelken et al, 1998). The only vascular bed to show vasodilatation in response to anandamide was the hindquarters, which is consistent with the eects of the synthetic cannabinoid, WIN 55212-2, in our model (Gardiner et al, 2001;2002a, b). We have shown that the hindquarters vasodilator responses to WIN 55212-2 are sensitive to CB 1 -receptor antagonism, and involve b 2 -adrenoceptors (Gardiner et al, 2002a, b).…”
supporting
confidence: 64%
“…However, in those cases, the hindquarters vasodilator eects were also inhibited by AM 251. Furthermore, at least with WIN 55212-2, the hindquarters vasodilatation was insensitive to ganglion blockade (Gardiner et al, 2001), leading us to speculate on the possibility of involvement of CB 1 -receptor-mediated release of adrenaline from chroman cells (Gardiner et al, 2002b). In contrast, in the case of anandamide, it appears that CB 1 -receptors are not involved.…”
mentioning
confidence: 72%
“…In contrast to the actions of anandamide, these cardiovascular effects were sensitive to the cannabinoid CB 1 receptor antagonist, AM251, but the hindquarters vasodilatation was also inhibited by a b 2 -adrenoceptor antagonist. Studies on conscious normotensive and hypertensive rats have also demonstrated pressor effects with WIN 55,212-2, which were sensitive to ganglion blockade (Gardiner et al, 2001). From these findings it was concluded that the effects of synthetic cannabinoids were mediated via CB 1 -receptors linked to increases in sympathetic activity.…”
Section: Studies In Conscious Animalsmentioning
confidence: 71%
“…This is mirrored by studies on anaesthetised animals that report hypotensive effects (Varga et al, 1995). However, findings in conscious animals are more complex and do not support the notion that cannabinoids are hypotensive agents (Stein et al, 1996;Lake et al, 1997;Gardiner et al, 2001;Gardiner et al, 2002a;Gardiner et al, 2002b). Similarly, there is no general consensus regarding the molecular target(s) for cannabinoids.…”
Section: Introductionmentioning
confidence: 77%
“…Whereas the physiological effects of WIN55212-2 via CB1 receptor mediation have been studied extensively (Aceto et al, 2001;Bridges et al, 2001;Gardiner et al, 2001;Simoneau et al, 2001), to our knowledge, there has been very little research on the metabolism of WIN55212-2 and other aminoalkylindole analogs, either in vitro or in vivo. Because of the remarkable structural difference between aminoalkylindoles and other cannabinoid ligands, it is hypothesized that AAIs could undergo biotransformations that also differ significantly from the metabolic patterns of the classical and nonclassical cannabinoids.…”
Section: Aminoalkylindoles (Aaismentioning
confidence: 99%